Feasibility of a novel self‐assembling submucosal injection peptide solution for endoscopic mucosal resection of colorectal lesions: A multicenter study - Keigo Sato; Takehide Fukuchi; Shinpei Kondo; Yuya Nakano; Yoko Hachisu; Kengo Kasuga; Ayako Matsui; Hironori Aoki; Kohei Takizawa; Shiko Kuribayashi; Yoji Takeuchi; Toshio Uraoka (DEN Open)
Abstract Objectives Although a novel submucosal injection material consisting of a fully synthetic, self‐assembling peptide solution, PuraLift, has recently become commercially available in Japan, there are a few reports regarding the usefulness of this solution. The aim of this study was to investigate the feasibility of PuraLift for conventional endoscopic mucosal resection (EMR) in clinical practice. Methods This multicenter retrospective study was conducted at the endoscopy units of five institutions from January 2023 to May 2023. Consecutive patients who underwent EMR with PuraLift for 5–20‐mm colorectal lesions were included in the introduction of this solution at each institute. The primary endpoint was the “effective resection” rate, defined as pathological complete resection, with “effective injection” defined as requiring no more than one additional injection due to adequate maintenance of mucosal lifting during EMR. Results In total, 110 lesions in 70 patients were treated by conventional EMR using PuraLift. En‐bloc resection was performed for 109 (99%) lesions, and complete resection was performed for 102 (93%) lesions. More than 95% of the lesions were neoplastic. Additional injections were required in only two lesions. Both were single additional injections, and the median overall injection volume was 1.5 mL. Therefore, the effective injection rate was 93% (95% confidence interval, 86%–96%). No adverse events occurred during the study period. Conclusions Although direct comparison with other materials is required, PuraLift seems feasible as an injection material for EMR.